Do high levels of home-ownership create unemployment? Introducing the missing link between housing tenure and unemployment. Issue 4 (19th May 2018) - Borg, Ida; Brandén, Maria
Abstract: A large number of studies have demonstrated that the proportion of home-owners in a region tend to be positively associated with the unemployment levels in that region. In this paper, we introduce a missing piece of explaining this commonly found pattern. By analysing individual-level population register data on Sweden, we jointly examine the effects of micro- and macro-level home-ownership on individuals' unemployment. The findings indicate that even though home-owners have a lower probability of being unemployed, there is a penalty for both renters and home-owners on unemployment in regions with high home-ownership rates. Differences in mobility patterns cannot explain this pattern. However, when labour market size is considered, the higher probability of unemployment in high home-owning regions is drastically reduced. This suggests that high home-ownership regions tend to coincide with small labour markets, affecting the job matching process negatively.